Radiotoxic fission products and radiological effects in the Mediterranean Sea biota from a hypothetical accident in Akkuyu Nuclear Power Plant - Abbasi, Akbar; Zakaly, Hesham M. H.; Almousa, Nouf (Pergamon-Elsevier Science Ltd, 2023)
A combined hydrodynamic/radiobiological model was used to calculate the distribution and dose rate of significant radionuclides in the Mediterranean Sea marine organisms in the event of an accident at the Akkuyu Nuclear Power Plant (ANPP). The Hybrid single-particle Lagrangian integrated trajectory (HYSPLIT) model was applied to simulate the dispersion and deposition of artificial radionuclide concentrations. Environmental Risk from Ionising Contaminants: Assessment and Management (ERICA) tools were utilized to assess issues related to sea health and potential hazards in case of an accident. The scenario source term profile was derived from the Fukushima nuclear power accident. Volumetric concentrations and deposition levels of pollutants increased from 1 MBqm- 3 to 1 x 103 MBqm- 3 and from 1 x 10-1 MBqm- 2 to 1 x 10-7 MBqm- 2 after 48 h. In terms of dose rates to the various marine biotas, polychaete worms had the greatest overall dose rate and the highest contribution to total dose rates attributable to 137Cs radionuclide.
Keywords: Mediterranean Sea; 137Cs; 131I and90Sr; Akkuyu Nuclear Power Plant (ANPP); HYSPLIT; ERICA